Developing career through community engagement: the Nigerian university experience - Adekalu, Samuel Olutokunbo; Ismail, Ismi Arif; Krauss, Steven Eric; Suandi, Turiman (Australian International Academic Centre, 2018)
So far, there has been no serious correction awareness aimed at addressing and promoting career development through community engagement practice in Nigeria, especially in academic settings. No research has been carried out to examine faculty members, particularly professors’ experiences in developing career through community engagement activities in the Nigerian universities. To address this gap, this article presents the perspectives of professors on how faculty members can be attracted to community engagement as a strategy to develop career and boost the reputation of their respective institutions that has been dominated by teaching and research. This article employed the qualitative method, interviewing nine professors from diverse academic disciplines in a leading conventional university in Nigeria. From the analysis, community engagements were found to foster academic career development of the professors in their areas of expertise. More specifically, participatory community engagement outreach helped in expansion of knowledge through solving practical problems, career growth through promotion earned, and increased job satisfaction. The study concludes with implications for human resource development practice and suggestions for future research.